Leisure Utilization Strategy During the Covid-19 Pandemic in Kualu Village Kampar Regency - Indrawati Indrawati; Risdayati Risdayati; Rina Susanti; Teguh Widodo (Institute of Computer Science (IOCS), 2022)
Limited space and increased availability of individual leisure time during the pandemic can be both a potential and a serious problem if not managed properly. The group of cemderung village mothers have more leisure time (leisure) than men. And dominant is not productively utilized. The target and target of this devotional activity is to provide an understanding of free time utilization strategies and basic skill training. With the target partner is the PKK mothers' group of Kualu village. The implementation of devotion activities is carried out by combining lecture and demonstration methods. The initial stages of the survey are conducted to identify the availability and utilization of the target group's free time. As a result, 65% of the target group had more than 4 hours of free time and only 56% were utilized for productive activities. 73% use it for non-productive activities. To make effective use of free time. Target groups are encouraged and trained to actively utilize leisure time with productive activities. Produce products that are worth selling and optimizing their potential. The strategy of using free time passively is done by training to save family expenses through making their own dish soap and processing coconut pulp into family snacks.